Peran Dai Perbatasan Aceh dalam Pembinaan Akhlak Masyarakat di Kecamatan Danau Paris Aceh Singkil - Abdul Manan; Mukhsin Nyak Umar; T. Lembong Misbah (Tadabbur: Jurnal Peradaban Islam, 2023)
This study aims to determine the role of Da'i in fostering Community Morals in Danau Paris, Aceh Singkil District. To what extent is the role of the da'i, what are the beliefs of the minority Muslim community, what are the supporting and inhibiting factors faced by the preacher at the research location. The method used in this research is qualitative. This method is carried out in relation to existing phenomena in the field by collecting data, especially from research informants. The data collection techniques used were interviews and documentation, the research subject was the role of the preacher in Danau Paris District, Aceh Singkil Regency. The results showed that the role of the preacher used was to invite and persuade the community to do good by filling in recitations, sermons Friday, educating children by reading Al-Qur’an, delivering religious lectures based on the Al-Qur’an and Hadits, which is a foundation from Allah SWT. The results achieved by the da'i in Danau Paris District in improving and fostering community morals have progressed and given drastic changes so that the da'i is declared successful in achieving da'wah by using this role.